The psychology of autonomy - Kaebnick, Gregory E. (The Hastings Center report, 2016)
In May 2016, right around the time that this issue of the Hastings Center Report should be published, The Hastings Center is holding a conference in New York City titled “Bioethics Meets Moral Psychology.” The goal of the conference is to consider the lessons that bioethicists should learn from the raft of literature now accumulating on how the mental processes of perception, emotion, and thinking affect things that bioethicists care about, from the education of health care professionals to the conflicts that arise in clinical care, the “culture wars” over bioethical policy issues, the status of different cultures’ value systems, and the very understanding of the values that are foundational in moral thinking. The articles in this issue simply provide more evidence that bioethics is meeting moral psychology.